Classifications of multicast routing In mobile ad hoc networks - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana (IIUM Press, 2011)
Multicasting is a useful communication scheme that facilitates group communication. Multicasting can improve the efficiency of the wireless link when sending multiple copies of messages. Multicast is a relatively unexplored research area, when it is compared with Unicast [I]. Over the past few years, several multicast routing protocols have been proposed for Ad-Hoc networks. In this chapter, we first provide a classification approach of the multicasting techniques in mobile Ad-Hoc networks, followed by the description of theexisting approaches that support QoS in mobile Ad-Hoc networks using multicasting scheme. We concentrate on hierarchical multicast routing protocols and position-based protocols, because of its relationship to our research. We will highlight their advantages and outline their limitations